Omphalocoeles: A decade in review - Simmi Singh; Anil Madaree (South African Medical Association, 2016)
Background. Omphalocoeles are associated with significant morbidity and mortality. The presentation varies greatly and management options differ accordingly. Limited literature exists regarding the varied presentation, associated congenital abnormalities and survival from a South African, or even an African perspective. Objective. To describe the presentation of omphalocoeles, associated abnormalities and survival rates. Methods. A retrospective epidemiological chart review of patients referred to the paediatric surgical service with newly diagnosed omphalocoeles, between January 2002 and December 2012. Data retrieved included patient demographics, perinatal history, HIV status, associated abnormalities, size of the omphalocoele, management and outcome. Results. One hundred and fifty-four patients were diagnosed with an omphalocoele during the study period. There were 117 (75.9%) associated congenital abnormalities, 64 (41.5%) minor omphalocoeles (defined as <5 cm) and 66 (42.8%) major omphalocoeles (defined as >5 cm). Eleven patients (7.1%) had ruptured omphalocoeles. Beckwith-Wiedemann syndrome was the most commonly associated abnormality (37.6%), followed by cardiac defects (34.4%). Conclusion. Omphalocoeles are associated with high numbers of congenital abnormalities. This further complicates management in a resource-poor environment. There is an increased association with Beckwith-Wiedemann syndrome compared with previous studies. This highlights the need to be vigilant with glucose monitoring and to prevent secondary, avoidable complications.